Time of day effects on speed, change of direction speed and reactive agility in adolescent soccer players - Gusic, M.; Molnar, S.; Madic, D. (World Congress of Performance Analysis of Sport XII, 2018)
Purpose: Most of the studies consistently reported higher performance in the afternoon than the morning. However, data examining the effect of time-of-day on agility performances appear to be equivocal. This study investigated the effects of time-of-day on speed, change of direction speed and reactive agility in young soccer players. Methods: Fifty-one soccer players from Serbia (age: 17.4±0.7 yr; weight: 72.4±4.3 Kg: height: 182.3±4.4 cm; experience: 6±1 yr) volunteered to participate in this study. Soccer players participated in the testing at two times a day: 08:00 and 18:00 h in a randomized order over two days with a minimum recovery period of 36 h. The running speed of players was determined using a 20-m sprint effort with photocell gates (Microgate, Polifemo Radio Light. Italy) placed 0.4 m above the ground, with an accuracy of 0.001 ms. The timer was automatically activated as participants crossed the first gate at the starting line with split times at 5 m. and 10 m. Change of direction (COD) speed was measured with Illinois agility test and Y test to the left and to the right side. The reactive agility test (RAT) was performed according to the protocol described previously by Chaouachi et al. (2014). During RAT. the tester had 4 options for each condition: preplanned and randomly ordered (i.e.. 8 trials). All these conditions were provided to each player in 2 series (5-8 minutes between sets rest) in a random order. Players were instructed to recognize the cues as soon as possible. Running time was recorded using photocell gates (Microgate. Polifemo Radio Light. Italy) placed 0.4 m above the ground, with an accuracy of 0.001 ms. The same conditions were used for another reactive agility test but this time the Witty SEM lights were used instead the testers. When the participants past the first gate the signal shows right or left direction. The participants must react to visual signal, change direction and past the third gate. Results: There were no significant differences between morning and evening testing for speed in adolescent soccer players (p>0.05). Reactions on both signals in RAT tests were significantly higher in the evening than the morning (P<0.05). However, results for Illinois (p-0.001) and Y test (left: p=0.006 and right: p=0.001) were significantly better in the morning than in the evening. Conclusion: The present study confirms daily variations in change of directions and agility performance in trained young Serbian soccer players. However, the present results indicate that the samples of junior soccer players displayed an optimum for selected soccer-specific skills in the evening, which is in contrast to change of direction speed results. Nevertheless, the coaching staff should be aware of these rhythms and plan activities accordingly.